2021
DOI: 10.1002/casp.2553
|View full text |Cite
|
Sign up to set email alerts
|

Prosociality during COVID‐19: Globally focussed solidarity brings greater benefits than nationally focussed solidarity

Abstract: Many charities are appealing for donations to address problems caused by the COVID‐19 crisis. Two survey studies (total N = 500) tested predictors of donation intentions of British participants to help those suffering from the crisis in Britain (ingroup donations) and overseas (outgroup donations). Perceptions of international, global common fate in our success in managing and overcoming the crisis was positively associated with prosocial intentions towards both national ingroup and outg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
31
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 34 publications
3
31
0
Order By: Relevance
“…The results of Barragan and colleagues' [23] study documented that identification with all humanity can be considered "the most consistent and consequential predictor of individuals' cooperative health behavior and helpful responding" during the COVID-19 pandemic [23] (p. 1). Zagefka's [60] research on prosociality during COVID-19 showed that a focus on global solidarity (also in the form of identification with all humans) enhanced helping within-and across-group boundaries. Thus, examinations of global human identity and COVID-19 attitudes and behaviors, including our study, showed that such a broad identification may be especially potent in promoting prosocial attitudes and behaviors that contribute to protecting fellow humans during a global pandemic [61].…”
Section: Discussionmentioning
confidence: 99%
“…The results of Barragan and colleagues' [23] study documented that identification with all humanity can be considered "the most consistent and consequential predictor of individuals' cooperative health behavior and helpful responding" during the COVID-19 pandemic [23] (p. 1). Zagefka's [60] research on prosociality during COVID-19 showed that a focus on global solidarity (also in the form of identification with all humans) enhanced helping within-and across-group boundaries. Thus, examinations of global human identity and COVID-19 attitudes and behaviors, including our study, showed that such a broad identification may be especially potent in promoting prosocial attitudes and behaviors that contribute to protecting fellow humans during a global pandemic [61].…”
Section: Discussionmentioning
confidence: 99%
“…The results also confirm the importance of a perception that the fate of the ingroup is shared with others around the world. As seen in other contexts (e.g., Ntontis et al, 2020 ; Zagefka, 2021b ), a sense of shared adversity or shared destiny can have powerful consequences for behavioural choices, especially in the face of disaster events. In the context of the current coronavirus crisis, indeed social scientists have highlighted the importance of shared identity and social cohesion for generating compliance with measures that might be inconvenient for individals but that are essential for the management of the pandemic for society as a whole (e.g., Miller, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…During times of crises such as the COVID-19 pandemic as well as natural disasters like earthquakes and hurricanes (Maki et al, 2019), prosociality or prosocial behavior (PsB) has been of interest to researchers. Zagefka (2021) tested the predictors of people's intentions to make donations to help those suffering from crises created by the COVID-19 pandemic in the United Kingdom (U.K.) and concluded that perceiving a common fate in the context of a crisis was associated with PsB. The evidence also reveals that PsB exerts positive effects on the helpers, decreasing their stress and loneliness and increasing social connection, solidarity, happiness, and shared resilience (Zaki, 2020).…”
Section: Introductionmentioning
confidence: 99%